Body measurements of Sudan desert sheep lambs fed urea ensiled groundnut hulls and molasses under range conditions (Journal of Veterinary Medicine and Animal Production, 2021)
The study was conducted to evaluate the effect of feeding urea-treated groundnut hulls (silage) and molasses on body measurements of Hammari desert sheep lambs, at Elnuhood Desert Sheep Research Station, North Kordofan State, to meet the feed shortage during summer. The duration of the experiment was ninety days. Sixty desert sheep lambs (thirty males + thirty females) of 6 months age and 23.4 kg average live weights were divided into three equal groups (A, B and C). Groundnut hulls treated with 5 % urea was ensiled for 30 days. The lambs were fed a ration containing 77% silage and 23% molasses in addition to natural pasture grazing. Group A was offered 400gm silage and 120 gm molasses per day, group B was offered 200 gm silage and 60 gm molasses per day and group C (the control) was left to graze the natural pasture without supplementation. The effects of feeding management and sex were determined. The result revealed that, the slaughter weights were not significantly different among the treatments, group A gave the highest weight (26.25kg) followed by group B (23.69kg) while group C had the lowest weight (22.25kg). The body measurements were not significantly different among the supplemented groups except the heart girth which was significantly higher in group A (68.9cm) compared with group B (67.1cm) and the control, group C (67.4cm). Males had significantly (p